2011
DOI: 10.1038/mt.2010.267
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated Virus Vectors Serotype 2 Induce Prolonged Proliferation of Capsid-Specific CD8+ T Cells in Mice

Abstract: Using adoptive transfer models we determined that an adeno-associated viral vector of serotype 2 (AAV2) induces in mice proliferation of CD8(+) T cells that recognize an epitope within the viral capsid. Proliferation to an endogenous epitope within viral protein (VP)3 could be observed for at least 3 weeks while a foreign epitope placed at multiple copies within VP2 elicited CD8(+) T cell expansion for at least 10 weeks. These data show that capsid antigens of AAV2 degrade slowly over a period of weeks and dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…by guest www.bloodjournal.org From corresponding receptors for several weeks following hepatic transfer of the vector. 29 It is possible that cell lysis as tested here requires higher levels of surface-expressed MHC I-peptide complexes compared with T-cell proliferation as was tested in our previous studies. Nonetheless, there is another interesting similarity between the mouse model and clinical studies.…”
Section: Ctl-mediated Killing Is Less Efficient Against Hepatocytes Tmentioning
confidence: 92%
See 1 more Smart Citation
“…by guest www.bloodjournal.org From corresponding receptors for several weeks following hepatic transfer of the vector. 29 It is possible that cell lysis as tested here requires higher levels of surface-expressed MHC I-peptide complexes compared with T-cell proliferation as was tested in our previous studies. Nonetheless, there is another interesting similarity between the mouse model and clinical studies.…”
Section: Ctl-mediated Killing Is Less Efficient Against Hepatocytes Tmentioning
confidence: 92%
“…Immunization against capsid by various methods designed to induce capsid-specific CD8 1 T cells failed to eliminate transduced cells in mice, 20,24-28 despite major histocompatibility complex class I (MHC I) presentation of capsid for several weeks following AAV gene transfer. 29 A more recent study showed some effect when a strong heterologous CD8 1 T-cell epitope was incorporated into the capsid. 30 Surprisingly, nonhuman primates, who are also natural hosts for AAVs, have also not been suitable models.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple attempts to generate a mouse model failed. [74][75][76] More recent attempts that have made use of systems that increase the frequency of epitope-specific T cells (incorporation of SIINFEKL peptide epitopes into the AAV vector capsid and use of OT-1 mice 77 ), or that further promote the adaptive immune response through the use of adjuvants, 78 have allowed recapitulation of some features of the human response to AAV-mediated liver-directed gene transfer, but their utility in devising solutions in humans remains to be demonstrated. Because NHPs are also natural hosts for some serotypes of AAV, it seemed logical that one could model the human immune response in these animals, but multiple attempts to do so have also failed.…”
Section: Immune Responses In Aav Gene Therapy 25mentioning
confidence: 99%
“…They combine several advantageous features, including a good safety profile, stable long-term gene expression in several tissues, the ability to transduce dividing and nondividing cells, and physicochemical stability (11,66). AAV vectors show generally a low innate immunity, as well as low efficiency to transduce professional antigen-presenting cells (87), although recent studies warrant a more differentiated view of the immune response to AAV-mediated gene transfer (8,22,23,26,29,32,33,37,50,65,84,88). Humoral immune responses are generated and memory CD8 ϩ T-cell responses have been observed in clinical trials (36,40,58).…”
mentioning
confidence: 99%